A newly discovered sRNA is involved in the virulence regulation of Salmonella pullorum - He, Ting; Huang, Meiling; Sun, Yuling; Ding, Yonghui; Zhou, Nanlong; Fu, Meihong; Li, Tiansen (Frontiers in Veterinary Science, 2025)
BackgroundSalmonella pullorum, the primary pathogen responsible for avian pullorum disease, has imposed substantial economic losses on the poultry industry. sRNAs, a class of small non-coding RNAs, have been identified in numerous bacterial species and serve as pivotal regulatory factors in bacteria.MethodsA bacterial infection assay was conducted to detect the differential transcription levels of sRNA12 in the macrophage cell HD11. Environmental stress tests, intracellular survival assays, target gene transcription analyses and chick virulence tests were conducted to compare the wild-type strain and the ΔsRNA12 deletion strain.ResultsA significant 7.5-fold increase in the transcription level of sRNA12 was observed during the invasion of host cells by bacteria. Under hyperosmotic conditions, the survival ability of the deletion strain was markedly reduced, while in a highly oxidative environment, it was significantly enhanced. Compared with the wild-type strain, the colonization ability of the ΔsRNA12 deletion strain in HD11 cells was enhanced by 3.5-fold. The transcription levels of most target genes of sRNA12, such as ompD, siiE, and prgH, were significantly upregulated. The LD50 of the deletion strain in chicks was approximately three times lower than that of the wild-type strain. Moreover, the colonization abilities of the deletion strain in the liver, spleen, and cecum of chicks were significantly enhanced and it induced more severe organ lesions.ConclusionThe findings suggest that the deletion of sRNA12 enhances the virulence of S. pullorum. This research provides novel insights into elucidating the pathogenic mechanism of S. pullorum and the associated regulatory signaling pathways.